Properties of acrylonitrile-butadiene-styrene/polycarbonate blends with styrene-butadiene-styrene block copolymer - TAŞDEMİR, MÜNİR (WILEY, 2004)
The importance of alloys and blends has increased gradually in the polymer industry so that the plastics industry has moved toward complex systems. The main reasons for making polymer blends are the strengthening and the economic aspects of the resultant product. In this study, I attempted to improve compatibility in a polymer blend composed of two normally incompatible constituents, namely, acrylonitrile-butadiene-styrene (ABS) and polycarbonate (PC), through the addition of a compatibilizer. The compatibilizing agent, styrene-butadiene-styrene block copolymer (SBS), was added to the polymer blend in ratios of 1, 5, and 10% with a twin-screw extruder. The morphology and the compatibility of the mixtures were examined by scanning electron microscopy and differential scanning calorimetry. Further, all three blends of ABS/PC/SBS were subjected to examination to obtain their yield and tensile strengths, elasticity modulus, percentage elongation, Izod impact strength, hardness, heat deflection temperature, Vicat softening point, and melt flow index. (C) 2004 Wiley Periodicals, Inc.
Keywords: alloys; blends; compatibilization; elastomers; polycarbonates; ABS